Adaptive Particle Swarm Algorithm for Parameters Tuning of Fractional Order PID Controller - Chaobo Chen; Li Hu; Lei Wang; Song Gao; Changhong Li (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexIn order to optimize the parameters of fractional order PID controller of complex system, an adaptive particle swarm optimization (PSO) method is proposed to realize the parameters adjustment. In this algorithm, the tuning particle population is divided into three subgroups firstly, and through introducing the swarm-aggregation degree factor and the evolution speed factor of particle, dynamically adjusting the inertia weight and size of subgroups respectively, setting to find optimal objective according to the time-domain performance index of the system, and then the controller parameter tuning is realized by iterative calculation. Finally, adaptive particle swarm optimization method of fractional order PID controller is applied to integer order and fractional order of the controlled system for performance simulation in time domain analysis. The experimental results show that the proposed method could improve the performance of the control system and has strong anti-interference ability.